Customer happiness and open innovation in the esthetics education for the elderly generation - Kyu-Ok Shin; Na-Gyeong Yeom; Hang-sik Park (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
In Korean society, where aging is rapidly progressing, the happiness of the elderly is no longer an economic issue. An esthetics program has the effect of improving depression or low self-esteem to increase psychological and physical satisfaction, which is a good way to raise the happiness index of the elderly. However, there is a lack of esthetics education or esthetics programs in Korea to train estheticians to serve elderly people. This study confirmed the possibility of open innovation through esthetics education to increase the happiness index of the elderly. As a research method, a self-administered questionnaire was used to survey 572 estheticians and analyzed statistically. In this study, Korean estheticians were very positive about the need for the development of professional care programs for the elderly, and it was found that they are willing to care for the elderly. Developing a variety of esthetic programs through the training of professional manpower for the elderly in the future will contribute to enhancing the happiness index of elderly Korean people.
Keywords: 650; aging; education; elderly generation; esthetics service; happiness index